Identifikasi Potensi Glaukoma dan Diabetes Retinopati Melalui Citra Fundus Menggunakan Jaringan Syaraf Tiruan - Muhammad Ezar Al Rivan; Tegar Juangkara (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2019)
Glaucoma and diabetic retinopathy identification conduct form fundus image. Artificial Neural Network can be used as algorithm to identify glaucoma and diabetic retinopathy. Dataset contains 60 fundus image consist of 20 glaucoma fundus image, 20 diabetic retinopathy fundus images and 2- normal fundus image. The result are 86,6% for average recall, 86,6% for average precision and 91,06% for average accuracy.